Respuesta :

Answer:

There are a few rules that we can use here:

ln(a^x) = x*ln(a)

ln(a) - ln(b) = ln(a/b)

ln(1) = 0

So here we want to expand:

ln(1/49^k)

First we can use the second property to get:

ln(1/49^k) = ln(1) - ln(49^k)

using the third property, we have:

ln(1/49^k) = ln(1) - ln(49^k) = 0 - ln(49^k)

ln(1/49^k) =  - ln(49^k)

Now we can use the first property to get:

ln(1/49^k) =  - k*ln(49)

Now we can use the fact that:

49 = 7*7 = 7^2

then:

- k*ln(49) = -k*ln(7^2) = -2*k*ln(7)

So we have:

ln(1/49^k) = (-2*ln(7))*k

We can expand it anymore because this is a real number  "(-2*ln(7))" times a variable k.

ACCESS MORE